Critical Race Structuralism and Charles Mills' Racial Contract: Pedagogical Practices for Twenty-first-century Educators. Issue 4 (October 2022) - Wiggan, Greg; Teasdell, Annette; Parsons, Tierra
At the nexus of legislation and education lies a vigorous debate regarding teaching about racial and ethnic relations in U.S. schools. Applying critical race structuralism (CRS), a new contribution to the field, this research explores Charles Mills' Racial Contract as a pedagogical tool to help meet the needs of twenty-first-century learners. The article examines the following question: How can teaching Charles Mills' Racial Contract from a CRS perspective expand pedagogical practices for educators? The findings suggest that applying CRS can help prepare educators to engage learners in diversity, equity, inclusion (DEI), and beyond. This work has implications for teachers, students, policy makers, and global citizens interested in mediating the effects of racism in schools and society.